O papel dos atores sociais do mercado de reciclagem em Santarém: uma análise socioeconômica à luz do indicador força motriz-estado-resposta - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The objective of the study is to analyze the socioeconomic implications of the recycling market in the Santarém, Para, Brazil, based on the Sustainability Indicators System Driving Force-State-Response - FSR. The complexity of the theme makes it essential to use sustainability indicators to understand the interrelationships and interdependence among the social actors in the management of solid urban waste and the pressure resulting from the construction of their identity. The study used ethnomethodology as a methodological approach, using semi-structured interviews, photographic records, on-site observations, and public documents and databases. Then, questionnaires were applied, incorporating the dimensions of the FSR model in the Minitab 11 computational tool. Econometric analysis was conducted through Stepwise regression, considering only the primary sector, since it was determined that these actors are determinants of the main challenges and conflicts perceived in the market. The interaction among the actors occurs in a disconnected way, both within the economic sectors and between them. The social and cultural differences between the two cooperatives influence their expectation with respect to recycling. The organization of the production park facility follows a more homogeneous pattern, with the industry having greater identification with the recycler market. In the primary sector, social indicators such as Driving Forces and Pressures predominate and the economic and environmental dimensions represent their State indicators. In the Productive Park, the Driving Forces are in the economic indicators and the quality of the resources (the State) permeates all the dimensions of the sustainability. Due to the productive park facility selection of workers among scavengers, there is positive causality that their workers demonstrate identification with the activity. As a Response to the industrial standard, environmental monitoring is part of the process of these companies. Efficiency and equity issues are common, effective support from municipal public agencies is important to enable poverty reduction, as is the inclusion of individuals and companies involved in materials recycling.
Keywords: Implicações socioeconômicas; Mercado de reciclagem; FMER; Indicadores de sustentabilidade; GRSU; CNPQ::CIÊNCIAS HUMANAS; PROCESSOS DE URBANIZAÇÃO NA AMAZÔNIA E SUSTENTABILIDADE; SOCIEDADE, NATUREZA E DESENVOLVIMENTO